Cost comparison analysis of slab structure using concrete beam and steel beam - Yopi Lutfiansyah; Galen Tanjung (Journal of Applied Science, Engineering, Technology, and Education, 2020)
Cost planning is an important phase on construction project planning to give illustration to the owner how much cost they should spend to execute that project. The slab is an element of the structure that has a large amount of the quantity so that affects the cost of the whole project. Then the cost comparison of slab structure has to be analyzed to know the most optimum design between conventional shuttering with the concrete beam on the initial design, first alternative options design, and metal deck shuttering with steel beam on second alternative design. The calculation of the slab structure cost analysis were based on Indonesia’s standard (PermenPUPR and SNI). The result is the first alternative options design that using concrete beam were cheaper 10,24% than the initial design that using concrete beam too while the second alternative options design that using steel beam were more expensive 27,14% than the initial design.